Two margins of informality - Cisneros-Acevedo, Camila (2020)
The ILO (2018) report shows that more than 61 per cent of the world's employed population work informally, most of them in emerging and developing countries. The majority lack social protection, rights at work, and decent working conditions. The ILO emphasizes that a transition to a formal economy is a condition to realize decent working conditions for all. Despite its importance, informality still lacks a universal definition. Throughout this thesis, I consider two margins of informality. The extensive margin, where firms do not register their business; and the intensive margin, where legally established firms do not pay mandatory contributions such as retirement and health insurance on behalf of their workers.